Hegel og Kierkegaard i religionsfilosofisk perspektiv: Med fokus på åbenbaringsbegrebet og forsoningstanken - Karlsen, Mads Peter (Dansk Teologisk Tidsskrift, 2025)
Following the lead of philosophers of religion Paul Ricœur and Michael Theunissen, this article revisits the long-standing, but still vital debate on how to understand the relationship between Hegel and Kierkegaard and the theological implications of this relationship. The first part of the article proposes a dialectical reading guided by a mutually critical mirroring of Kierkegaard in Hegel and Hegel in Kierkegaard. The second part of the article outlines the Hegelian preconditions of Kierkegaard’s philosophy of religion, highlighting two decisive points of intersection. The following part investigates the contrast between Hegel’s notion that in Christianity God is fully revealed and Kierkegaard’s conception of revelation as absolute paradox. This leads to a detailed consideration in the fourth and last section of how Hegel and Kierkegaard differ in their understanding of reconciliation and sin.